Bone Regeneration in Iliac Crestal Defects: An Experimental Study on Sheep - Scarano, Antonio (Biomed Res Int, 2016)
Background. Oral rehabilitation of partially fully edentulous patients with dental implants has become a routine procedure in clinical practice. In a site with a lack of bone GBR is a surgical procedure that provides an augmentation in terms of volume for the insertion of dental implants. Materials and Methods. In the iliac crest of six sheep 4 defects were created where an implant was inserted, three of them with different biomaterials and a control site. All animals were sacrificed after a 4-month healing period. All specimens were processed and analyzed with histomorphometry. Statistical evaluation was done to evaluate percentage of bone defect filled by new bone. Results. All experimental groups showed an increase of the new bone. Higher and highly statistically significant differences were found in the percentages of bone defect filled by new bone in group filled with corticocancellous 250–1000 microns particulate porcine bone mix. Conclusions. This study demonstrates that particulate porcine bone mix and porcine corticocancellous collagenate prehydrated bone mix when used as scaffold are able to induce bone regeneration. Moreover, these data suggest that these biomaterials have higher biocompatibility and are capable of inducing faster and greater bone formation.